TIPOLOGI HUNIAN UNTUK GENERASI MUDA DI PLUIT, JAKARTA UTARA - Jason Halim Saputra; Stephanus Huwae (Jurusan Arsitektur dan Perencanaan, 2022)
Population growth is something experienced by many countries, including Indonesia. Population growth results in higher demand for new housing. This inversely proportional to the decreasing availability of land for new residential development. In big cities like Jakarta with a density of 10 million people, land for the construction of new housing is increasingly difficult, causing changes in the typology of urban dwellings.The